THE ROLE OF ARTIFICIAL INTELLIGENCE IN PERSONALIZED LEARNING ENVIRONMENTS - Selim, Aybeyan; Ali, Ilker (International Scientific Journal Vision, 2025)
Integrating Artificial Intelligence (AI) into personalized learning environments transforms traditional educational models by offering tailored learning experiences to individual students. AI-driven tools such as adaptive learning platforms, intelligent tutoring systems, and natural language processing enable real-time adjustments in instructional content based on each student’s performance and needs. These technologies enhance student engagement, provide continuous assessment, and empower educators with data-driven insights to support targeted interventions. While AI presents immense potential for scalable, flexible, and accessible education, challenges such as data privacy and the need for human oversight remain crucial. This paper explores the role of AI in revolutionizing personalized learning, its benefits and the future implications for education.